2015
DOI: 10.1021/jf5059705
|View full text |Cite
|
Sign up to set email alerts
|

Slow Digestion Property of Octenyl Succinic Anhydride Modified Waxy Maize Starch in the Presence of Tea Polyphenols

Abstract: The in vivo slow digestion property of octenyl succinic anhydride modified waxy corn starch (OSA-starch) in the presence of tea polyphenols (TPLs) was studied. Using a mouse model, the experimental results showed an extended and moderate postprandial glycemic response with a delayed and significantly decreased blood glucose peak of OSA-starch after cocooking with TPLs (5% starch weight base). Further studies revealed an increased hydrodynamic radius of OSA-starch molecules indicating an interaction between OSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Octenyl succinylation is going to substitute the hydroxyl groups of starch molecules for carbonyl groups of OSA. The insertion of these carbonyl groups to starch molecule structure confirmed through FT-IR spectroscopy [7,8,16,17]. The FT-IR spectra of the native and OSA-modified starches are presented in Figure 3.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Octenyl succinylation is going to substitute the hydroxyl groups of starch molecules for carbonyl groups of OSA. The insertion of these carbonyl groups to starch molecule structure confirmed through FT-IR spectroscopy [7,8,16,17]. The FT-IR spectra of the native and OSA-modified starches are presented in Figure 3.…”
Section: Resultsmentioning
confidence: 97%
“…Starch is the abundant ingredient of rice and starch granule size is the smallest and ranges from 2 to 8 μm. The tiny starch granules are caused to use in beverages and dressings, encapsulation of phytochemicals as a carrier in the delivery system, and as a fat replacer [13,14,15,16,17,18]. If rice starch has both hydrophilic and hydrophobic groups, it will also be available for emulsions and use in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…For the FTIR spectra of all these samples, a strong broad band, resulting from OH stretching vibration (hydroxyl groups of starch), appears at 3300 cm −1 ; the characteristic peak at 2928 cm −1 corresponds to the CH stretching vibration; the absorption peaks at 1153, 1079, and 998 cm −1 are attributed to CO bond stretching . Compared with native starch, the spectra of OSA‐starches show a new peak at 1722 cm −1 , which is attributed to the stretching vibration of ester carbonyl group (CO) . Moreover, the decreasing intensity of the wide peak at 3300 cm −1 also can be observed, indicating the substitution of hydroxyl groups in starch.…”
Section: Resultsmentioning
confidence: 98%
“…Chemical modification of starch is an alternative approach to produce highly functional starch . Octenyl succinic anhydride (OSA) modified starch (OSA‐starch), a typical chemically modified starch, is considered as an effective emulsifier due to the addition of bifunctional groups which are both hydrophilic and hydrophobic . Therefore, OSA‐starch is used in a variety of oil‐in‐water (O/W) emulsions, water‐in‐oil (W/O) systems, and pharmaceutical and industrial areas, especially in food production, due to their excellent filming properties and good emulsion‐stabilizing properties .…”
Section: Introductionmentioning
confidence: 99%
“…Many producers use emulsions from OSA starch as fat replacers in foods with high fat content. In addition, OSA starch also has a functional health characteristic that is slow digestibility so that it is very potential to be developed in the formulation of a variety of functional food products (Het et al, 2008;Peng et al, 2015). Many recent studies have shown that OSA starch is used in food formulations as a fat repalcer or emulsifier.…”
Section: Application Of Osa Starch As a Fat Replacermentioning
confidence: 99%